Motivation of Lecturers and Students in Implementing the Freedom of Learning Independent Campus Program - Naibaho, Hastuti; Pitaloka, Endang; Avianti, Widya (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2025)
The freedom of learning independent campus (MBKM) policy is aimed at preparing students who can adapt to change and are relevant to the needs of the times. The COVID-19 pandemic has accelerated MBKM implementation. After almost two years, an evaluation of MBKM implementation is needed. This research aims to find out how interested students are in the MBKM program and how motivated lecturers are in the MBKM program. A mixed method was used in this research. For quantitative data, researchers conducted a survey using a questionnaire as a research instrument. Three hundred twenty-nine students from universities implementing MBKM were respondents to this research. The data is then processed descriptively. Qualitative data was obtained from interviews and FGDs with 51 structural and nonstructural lecturers—39 students from the heads of student organizations involved in this study. The results show that students have quite an interest in MBKM. Likewise, the lecturers are very motivated by MBKM.